A Revolution in a Revolution: The Secret Police and the Origins of Stalinism in Czechoslovakia. Issue 1 (February 2018) - Pucci, Molly
This article examines the origins of the Stalinist secret police force, the StB, in Czechoslovakia between 1945 and 1954. By focusing on the biographies of its officials, it argues that there was not one, but two, secret police forces in this period, each recruited from a different "generation" of local communists. In pointing to the social conflicts and ideological tensions that characterized the communist secret police force in this period, it forwards a new interpretation of the party purges and motivations of secret police officials responsible for the radical political violence in Stalinist Europe in the early 1950s.